(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2004)
In this article, we talk about the influence of Positivism for the implantation, in Brazil, of republicanic system, in november, 1889. We took care of political and cultural atmosphere of Empire's last years, speaking about the outbreak of new ideas, these introduced by Comte's Positivism and Spencer's Evolutionism. We have studied the works of firsts brazilian positivists, in especial, of the called "not orthodoxes", who, in spite of following in general Augusto Comte's ideas, were not members of "Apostolado Positivista do Brasil". We have demonstrated that, if Positivism, the doctrine, gave the doctrinal "substractum" for the implantation, among us, of the republican system, "orthodoxes positivists", however, did not have any participation in Brazilian Empire's fall. Brazilian Empire's fall was the consequence of Benjamin Constant Botelho de Magalhães's preaching, a "not orthodoxe", at Military School. This preaching has produced the military conditions to destrone Casa de Bragança. After the implantation of Republic, the "orthodoxes positivists" followed it.